ANALYSIS OF ORGANIZATIONAL COMMITMENT THROUGH OCB ON EMPLOYEE PERFORMANCE - Ridwan, Muhammad (Dinasti Publisher, 2020)
This study aims to analyze the effect of organizational commitment on OCB and employee performance, OCB on employee performance, and analyze the effect of organizational commitment through OCB as an intervening variable on employee performance. The population is all employees who work at SPMI units of Private Universities in West Sumatra, amounting to 241 people. Of the 241 people taken 30 as a sample of validity and reliability so the remaining 211 people still exist. While the number of samples taken using the saturation sampling technique, which is a sampling technique by taking the entire population that is 211 samples. The data collection method uses the survey method, followed by the statistical method to test the hypothesis by path analysis. The results of this study indicate that organizational commitment has a positive and significant effect on OCB and employee performance, so does OCB has a positive and significant effect on employee performance. In addition, organizational commitment through OCB also has an influence on employee performance.